Analysis Of Verbal And Nonverbal Communication Methods In The Cast Of The Character Antigone Performance Of Sophocles' Play Antigone - Precillia, Monita; Arimbi, Dewi; Darmadi, Dedi (Institut Seni Indonesia Padangpanjang, 2023)
The study is based on the performance of the play Antigone by Sophocles. The aim is to analyze the way the cast uses body language, facial expressions, and voice intonation to convey messages and emotions of their characters. This research uses qualitative methods with text analysis, performance observation, and interviews. The study explains the various aspects of theatrical communication used in the cast of Antigone, providing an in-depth understanding of how communication can enrich the understanding of characters and stories in theatrical performances. The findings of this study are expected to deepen the understanding of theater arts practitioners and theater researchers, helping them develop more memorable interpretations and executions of characters in performing arts works. Furthermore, this research has the potential to enrich the repertoire of classical Greek literature and broaden the understanding of communication in modern performing arts.